Factors facilitative of Catholic Educational Associations of the Philippines (CEAP) superintendents' leadership in school reforms - Meneses, Merlinda M. (Animo Repository, 2003)
This research describes the factors facilitative of CEAP Superintendents' leadership in school reforms. The study uses the case study method. Data are gathered through questionnaires and were reinforced and validated through interviews with some of the respondent-school heads of the study. Information on the leadership style, flexibility and effectiveness of the superintendent-respondents was obtained using the Leadership Behavior Analysis II Scoring and Profile by Blanchard (1999). As perceived by both the superintendents themselves and the school heads, the superintendent-related factors that facilitated the superintendents' leadership functions are: (a) extensive educational training (b) linkages with local and international educational institutions (c) practical experience in school administration (d) professional qualifications (3) technical and administrative competence and (f) leadership capabilities. The school-related factors include school heads' qualifications and competence, qualified and competent, administrative and technical skills, leadership capabilities, and networking capability with the institutions related to education. The congregation/diocese-related factors include the Bishop's support for the diocesan superintendent, the congregation's support for the congregational superintendent, the position of the superintendent in the congregation's/diocesan's organizational structure, and the clarity of roles and functions of the superintendents. The following conclusions were made based on the findings of the study: 1) A congregational/diocesan superintendent must possess appropriate professional qualifications, vast experience in school management, leadership skills, extensive educational training, broad linkages with educational institutions, and technical and administrative competence. 2) System-wide and school-based reforms initiated by the CEAP schools superintendents are likely to be perceived as beneficial by the different stakeholders in education like the students, the teachers, the parents, and the community. These reforms are academic, financial, physical, structural and organizational in nature. 3) The factors that are likely to facilitate the superintendents' leadership in school reforms are superintendent, institution/school, and congregation/diocese related factors.